Mathematical and Software Foundations of Computing Machines, Complexes, and Computer Networks - Ruzimov Bahromjon Bakhodirjonovich (Journal of Innovation in Education and Social Research, 2024)
This article explores the mathematical foundations and software design principles that underpin computing machines, computational complexes, and computer networks. Focusing on modern developments in system architecture, algorithms, and network protocols, we delve into how these elements enable efficient computation, communication, and data processing in distributed systems. This study also addresses challenges in scalability, reliability, and security, proposing methods for advancing computational infrastructure.